2008
DOI: 10.1158/1078-0432.ccr-07-4453
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Intraoperative Radiotherapy Impairs the Stimulation of Breast Cancer Cell Proliferation and Invasion Caused by Surgical Wounding

Abstract: Purpose: After apparently successful excision of breast cancer, risk of local recurrence remains high mainly in the area surrounding the original tumor, indicating that wound healing processes may be implicated.The proportional reduction of this risk by radiotherapy does not depend on the extent of surgery, suggesting that radiotherapy, in addition to killing tumor cells, may influence the tumor microenvironment. Experimental Design: We studied how normaland mammary carcinoma cell growth and motility are affec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
203
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(228 citation statements)
references
References 38 publications
14
203
1
10
Order By: Relevance
“…It suggests that the difference in non-breast-cancer mortality could arise from an increase in mortality from EBRT toxicity, as one would think conventionally, as well as a reduction in mortality because of a potential beneficial effect of TARGIT. The latter is a radically new hypothesis that the local effect of TARGIT on the tumour bed by inhibiting cancer-stimulating cytokines 17 may spill over to reduce the systemic inflammatory response to trauma and have significant long-term systemic beneficial effects that might be protective against cardiac and cancer mortality ( Figure 28). This remarkable finding, albeit a non-randomised comparison, could potentially have far-reaching implications.…”
Section: Other Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…It suggests that the difference in non-breast-cancer mortality could arise from an increase in mortality from EBRT toxicity, as one would think conventionally, as well as a reduction in mortality because of a potential beneficial effect of TARGIT. The latter is a radically new hypothesis that the local effect of TARGIT on the tumour bed by inhibiting cancer-stimulating cytokines 17 may spill over to reduce the systemic inflammatory response to trauma and have significant long-term systemic beneficial effects that might be protective against cardiac and cancer mortality ( Figure 28). This remarkable finding, albeit a non-randomised comparison, could potentially have far-reaching implications.…”
Section: Other Analysesmentioning
confidence: 99%
“…13,15,16 This is perhaps surprising given evidence from three-dimensional whole-organ analyses of mastectomy specimens, > 60% of which host additional cancer foci, with 80% of these foci found remote from the index quadrant. 17 It appears that these cancers in other quadrants lie dormant, rarely manifesting clinically, and recurrences develop in the tissues immediately surrounding the primary tumour. This could be because of a tumour-promoting effect of the microenvironment of the surgical wound, 18 or the presence of morphologically normal cells in the peritumoural tissues, which may already be on the path of malignant progression, as evidenced by their loss of heterozygosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that wound fluids , drained from BC patients for 24 hours post-surgery (hereafter WF), are very rich in cytokines and growth factors and very efficiently stimulate proliferation, motility and invasion and that activation of p70S6K signaling is a common event following exposure of breast cancer cells to WF [10,24]. Figure 1), suggesting that the spectrum of activity for this inhibitor may vary depending from the cancer subtypes.…”
Section: Fs-115 Efficiently Suppresses P70s6k Activity In Breast Cancmentioning
confidence: 99%
“…Advocates for IORT cite several potential advantages of using this approach: including delivery of radiation immediately after surgery to prevent tumour cell proliferation; change in cytokines pattern into a less stimulating microenvironment, which is expected to reduce the local recurrence rates; and reduced risk of geographical miss 29,30 .…”
Section: Intra-operative Rt (Iort) Boost Using Low Energy X-ray (Levementioning
confidence: 99%